The impact of adverse patient events among German anesthesiologists: a cross-sectional survey on the second victim phenomenon (SeViD-X) - Bexten, Tobias; Roesner, Hannah; Bushuven, Stefan; Klemm, Victoria; Kamphausen, Anne; Strametz, Reinhard; Beck, Grietje (BMC anesthesiology, 2025)
Adverse patient events are an inevitable part of an anesthesiologist’s work. When such incidents occur, they may lead to significant emotional and psychological distress in healthcare providers—a phenomenon known as the Second Victim Phenomenon (SVP). While international evidence of SVP exists, data from German anesthesiologists remain scarce.